Evaluation of tuberculosis qualification for healthcare professionals: proposal of a systematic model (Research, Society and Development, 2021)
Objective: to propose a systematic model for the assessment of tuberculosis (TB) qualification for health professionals. Method: quantitative methodological investigation study, developed in the city of Porto Velho-RO, in three stages for the elaboration, content validation and pilot test of the evaluation instrument, to be applied in the qualifications in TB, after complying with the ethical precepts. The first instrument (pre and post-test), consisted of 18 questions divided into three sections. The second instrument (late post-test), was composed of two open questions. The validation of the instruments occurred based on the assessment of the clarity, relevance and pertinence of the questions by experts on the subject. Results: the instruments remained with the same number of items, but they were changed in terms of writing for better understanding. Conclusions: the evaluation instrument developed has content and appearance validity, and is compatible for the evaluation of TB qualification, as a feedback tool for managers and participants.